Notes on the genus Microscymnus Champion, 1913 (Coleoptera, Coccinellidae), with description of a new species - González, Guillermo (Zootaxa, 2026)
The taxonomic placement of the genus Microscymnus Champion, which has been associated with the tribe Cryptognathini, is discussed, and is transferred here to the tribe Argentipilosini. A new species of the genus, M. westerduijni sp. nov. from Peru is described.